THE ARCHITECTURE OF PESANTREN: CURRENT ISSUES, CHALLENGES AND PROSPECT FOR DESIGN FRAMEWORK - Nensi Golda Yuli; Ilya Fadjar Maharika; Frank Eckardt (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2023)
Pesantren (Islamic Boarding School) is an indigenous educational institution originally from Indonesia and perhaps a unique form of the traditional Islamic education system and spreading to Southeast Asia that neighbouring countries. However, studies on pesantren rarely address physical elements and architecture. Learning pesantren architecture challenges us with representation: definition, how to visualize its form and program, and the design. Finding a body of knowledge on pesantren to excavate